Introduction: East-Central and Central-East Europe as an Imagined Space for Shakespeare - Havlíčková Kysová, Šárka; Mišterová, Ivona (Multicultural Shakespeare: Translation, Appropriation and Performance, 2023)
The publication of the issue was supported by the International Visegrad Fund, project no. 22210007, titled “Crossing Borders with Shakespeare since 1945: Central and Eastern European Roots and Routes.” The project is co-financed by the Governments of the Czechia, Hungary, Poland and Slovakia through Visegrad Grants. The mission of the Fund is to advance ideas for sustainable regional cooperation in Central Europe.